1997
DOI: 10.1046/j.1365-2842.1997.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occlusal contacts in maximum intercuspation using the T-Scan system

Abstract: Different authors have questioned the reliability of the T-Scan system as a method for registering occlusal contacts. The number of tooth contacts resulting from four bites made in maximum intercuspation was analysed with T-Scan using time moment statistics. The results indicate that (1) the largest number of contacts occur in the molar region (2) variability between subjects is greater than variability within subjects, and (3) it is possible to identify the subject being tested in 90.3% of cases. The T-Scan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…The values obtained by multiplying the number of contact points and the value of the color scale from the load graph of T-scan were considered to be the occlusal forces on the right and left sides 11. To evaluate the distribution of the occlusal forces, the asymmetry index of occlusal force was calculated using the following formula.…”
Section: Resultsmentioning
confidence: 99%
“…The values obtained by multiplying the number of contact points and the value of the color scale from the load graph of T-scan were considered to be the occlusal forces on the right and left sides 11. To evaluate the distribution of the occlusal forces, the asymmetry index of occlusal force was calculated using the following formula.…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications have reported T-scan III to show good reproducibility of surface measurements and registration of relative forces14,17,18, and Koos et al17 has shown that readings are unaffected by changing the sensor or repeating measurements. Not only has T-scan been found to provide reliable results in the identification of occlusal contact distribution17,21,22, a study comparing the sensitivity of various occlusal indicators found T-scan to be the only indicator unaffected by saliva 23. Moreover, a 2002 study of the T-Scan II system found that the system provided adequate repeatability in examining the occlusal contacts of complete prosthesis users as well as dentate subjects 24…”
Section: Discussionmentioning
confidence: 99%
“…Contact area has frequently been measured with T-Scan II equipment (Tekscan Inc., Boston, MA, USA),16,17 which is a reliable method for the analysis and evaluation of occlusal contact distribution in maximum intercuspation. This value is calculated by multiplying the number of tooth contacts recorded by the T-Scan sensor by the size of a single pixel (1.6 mm 2 ), thus reflecting occlusal conditions.…”
Section: Discussionmentioning
confidence: 99%